A educação libertadora no contexto de hoje : entre exigência e esperança para emancipação humana - Botelho, Tiago Alberione da Silva (2020)
This research is linked to the Graduate Program in Education, in the line of research Training of Teachers and Public Educational Policies of the Federal University of Mato Grosso, Campus Rondonópolis. Its objective is to deepen and analyze Paulo Freire's thoughts and concepts, which are: liberating education, emancipation, hope, dialogue and awareness. Such concepts make us question why liberating education helps the subject to be emancipated, free and reflective in today's times. Liberating education helps the human being "to be more" and to be a better human being. In this context, questions arise: what is the importance of liberating education for today? Why do hope and emancipation give a great possibility to the human being to be more reflective, free and autonomous? What is the importance of this socio-political study today? The methodology used is of a qualitative nature, of a bibliographical nature. This dissertation is based on the thought of liberating education conceived by Freire, Gadotti and other authors who dialogue with Freirian thought around Brazilian education today. The purpose of liberating education is to contribute to the formation of the subject's reflexive-critical thinking, so that he can analyze society and make decisions in front of the world in which he is inserted. Thus, the emancipated being has as its political intentionality that can assume a future and social transformation. To be emancipated is to have the awareness of being able to find freedom, happiness and also democracy. For reflection on the theme of liberating education today, this study was limited to the analysis of the categories of awareness, dialogue, hope, autonomy and freedom as the foundation of Freire's educational thought for overcoming the condition of the oppressed and for assuming the role of historical subject, agent of social transformation. The research on liberating education has made it possible to highlight to the subject the knowledge, dynamization and application of Freire's method in the subject who wishes to be free. In the face of this, the subject recognizes and knows himself/herself as well as the other, so he/she can develop, improve his/her life and reintegrate into society. The hope in Freire's context is to aim, dream, act and seek for a more dignified and solidary life. As for liberation, it is an instrument with which, based on the reflection obtained from his knowledge, the subject puts into practice and frees himself from himself and the other. Therefore, the society desired by Freire, an open, free democracy, demands the hopeful struggle for human emancipation. Liberating education in today's context challenges all of society, especially educators as political agents, to rescue hope, dreams and the struggle for a better, just and fraternal world. To have hope in today's world means resistance and courage to launch the struggle for the construction of a project of civility that guarantees decent living conditions for every human being.